Two new genera of grasshoppers (Orthoptera, Acrididae, Melanoplinae) from Baja California, Mexico, with a regional key to the genera of Melanoplinae - JoVonn G. Hill (ZooKeys)
Baja California, a 1,300 km long peninsula, exhibits considerable ecological diversity, encompassing coastal chaparral, coniferous forests, low desert scrub, and tropical deciduous forests. The region’s ecological complexity reflects its biogeographic history, marked by separation from mainland Mexico 5.5 million years ago. Survey efforts have documented an impressive 4,000 plants, and insect efforts have targeted bees, weevils, ants, and blow flies. Grasshoppers, in contrast, remain underexplored. The present study expands on expeditions from the 1970s to 2010s that focused on the peninsula’s Orthoptera. Two new genera are established—Bajatettix and Ozmacris—and a key to the genera of the Melanoplinae of the peninsula is provided. This study highlights the importance of understanding Baja California’s grasshopper diversity to support conservation initiatives and future ecological studies.